Candida albicans Filamentation Does Not Require the cAMP-PKA Pathway In Vivo - Rohan S. Wakade; Juraj Kramara; Melanie Wellington; Damian J. Krysan (mBio, 2022)
ABSTRACT Candida albicans is one of the most prevalent human fungal pathogens. Its ability to transition between budding yeast and filamentous morphological forms (pseudohyphae and hyphae) is tightly associated with its pathogenesis. Based on in vitro studies, the cAMP-protein kinase A (PKA) pathway is a key regulator of C. albicans morphogenesis. Using an intravital imaging approach, we investigated the role of the cAMP-PKA pathway during infection. Consistent with their roles in vitro, the downstream effectors of the cAMP-PKA pathway Efg1 and Nrg1 function, respectively, as an activator and a repressor of in vivo filamentation. Surprisingly, strains lacking the adenylyl cyclase, CYR1, showed only slightly reduced filamentation in vivo despite being completely unable to filament in RPMI + 10% serum at 37°C. Consistent with these findings, deletion of the catalytic subunits of PKA (Tpk1 and Tpk2), either singly or in combination, generated strains that also filamented in vivo but not in vitro. In vivo transcription profiling of C. albicans isolated from both ear and kidney tissue showed that the expression of a set of 184 environmentally responsive genes correlated well with in vitro filamentation (R2, 0.62 to 0.68) genes. This concordance suggests that the in vivo and in vitro transcriptional responses are similar but that the upstream regulatory mechanisms are distinct. As such, these data emphatically emphasize that C. albicans filamentation is a complex phenotype that occurs in different environments through an intricate network of distinct regulatory mechanisms. IMPORTANCE The fungus Candida albicans causes a wide range of disease in humans from common diaper rash to life-threatening infections in patients with compromised immune systems. As such, the mechanisms for its ability to cause disease are of wide interest. An intensely studied virulence property of C. albicans is its ability to switch from a round yeast form to filament-like forms (hyphae and pseudohyphae). Surprisingly, we have found that a key signaling pathway that regulates this transition in vitro, the protein kinase A pathway, is not required for filamentation during infection of the host. Our work not only demonstrates that the regulation of filamentation depends upon the specific environment C. albicans inhabits but also underscores the importance of studying these mechanisms during infection.